ANALISIS PENGARUH CAPITAL ADEQUACY RATIO (CAR) DAN LOAN TO DEPOSIT RATIO (LDR) TERHADAP KREDIT INVESTASI DI INDONESIA (STUDI KASUS BANK PERSERO TAHUN 2009 - 2015) - B21112045, Evi Novia Trisanti (Jurnal Curvanomic, 2016)
Bank is a financial institution that has a function as a financial intermediary between the parties and the excess funds were underfunded. Banks accept deposits from the public and channel them back into the community in the form of credit. This study aims to measure the Effect of Capital Adequacy Ratio (CAR) and the Loan to Deposit Ratio (LDR) Against Credit Investment In Indonesia Year 2009-2015 (monthly). This study uses Owned Banks in Indonesia. For the analysis process in need of secondary data taken from a variety of documentation, or publications from the various authorities and agencies such as the publication of the report of Bank Indonesia. In the analysis process, the program uses Eviews-7. Data-processing technique used is multiple linear regression, hypothesis testing while using t - test to test the effect of partial variables and test - F to test the effect of variables simultaneously with a significance level of 5%. It also performed classical assumption that include normlitas test, test multicollinearity, heteroscedasticity test and autocorrelation test. Based normality test, multicollinearity, heteroscedasticity test and autocorrelation test, there was no deviation from the classical assumptions. This indicates that the available data are qualified to use a multiple linear regression model. The results of analysis that the Capital Adequacy Ratio (CAR) and the Loan to Deposit Ratio (LDR) positive and significant impact on the investment loan. KeywordsÂ Â  : Investment Loans, Capital Adequacy Ratio (CAR), and Loan to Deposit Ratio (LDR)